Liquid and liquid-like surfaces/coatings that readily slide fluids. (December 2021) - Buddingh, Jasmine V.; Hozumi, Atsushi; Liu, Guojun
Abstract: While superhydrophobic structured surfaces have been studied extensively, they do not readily repel low surface tension liquids. Recently developed liquid and liquid-like surfaces, however, offer excellent sliding properties for multiple liquids regardless of their surface tensions. This review outlines recent progress on liquid-like monolayers, polymer brushes and hybrid films, as well as liquid surfaces such as slippery liquid infused porous surfaces (SLIPS), organogels and other non-traditional smooth surfaces. These surfaces/coatings are evaluated primarily on their dynamic dewetting characteristics, preparation techniques, durability, and additional functionalities when applicable. A future outlook for this field is also provided, emphasizing the need to balance the durability of the slippery properties with the simplicity/scalability and environmental impact of the design to achieve technologies that are suitable for large-scale production. Graphical abstract: Image, graphical abstract